Effect of the Anomeric Configuration on the Micellization of Hexadecylmaltoside Surfactants - Larsson, Johan (Langmuir : the ACS journal of surfaces and colloids, 2019)
The self-assembly of the two anomeric forms of n-hexadecyl-d-maltopyranoside (denoted α-C16G2 and β-C16G2) has been studied in dilute aqueous solution by means of surface tension measurements, scattering methods (dynamic light scattering, static light scattering, and small-angle X-ray and neutron scattering), and cryo-transmission electron microscopy at different surfactant concentrations and temperatures. Surface tension measurements demonstrate differences in the surfactant adsorption at the air-water interface, where α-C16G2 shows a lower CMC than β-C16G2. Similarly, micelle morphology was found to profoundly depend on anomerism. β-C16G2 preferentially forms very elongated micelles with large persistence lengths, whereas α-C16G2 assembles into smaller micelles for which the structure varies with concentration and temperature. The differences between the two surfactant anomers in terms of self-assembly can be attributed to the interaction between neighboring headgroups. Specifically, β-C16G2 allows for a closer packing in the palisade layer, hence reducing the micelle curvature and promoting the formation of more elongated micelles. Strong intermolecular headgroup interactions may also account for the observed rigidity of the micelles